New Research on Silicon (IntechOpen, 2023)
The knowledge of fundamental silicon questions and all aspects of silicon technology gives the possibility of improvement to both initial silicon material and devices on silicon basis. The articles for this book have been contributed by the much respected researchers in this area and cover the most recent developments and applications of silicon technology and some fundamental questions. This book provides the latest research developments in important aspects of silicon including nanoclusters, solar silicon, porous silicon, some technological processes, and silicon devices and also fundamental question about silicon structural perfection. This book is of interest both to fundamental research and to practicing scientists and also will be useful to all engineers and students in industry and academia.